Framing and analyzing ISIS through classical management perspectives (Journal of the Spanish Institute for Strategic Studies, 2019)
The formulation and implementation of effective counterterrorism strategies require a robust understanding of the dynamics and inter-related organizational elements of the outfits being combated in order to have a balanced all-round view of their strong points and the weak zones that can be focused upon for more efficient operations. Focusing on ISIS and the Jihadist Lone Wolf type, the threats they pose to the Spanish society can be better countered through a proactive approach also underpinned by the imperatives of the organizational elements of these organizations. Supplementing the existing frameworks being used by agencies, an invaluable perspective would be to observe the business and management dynamics within these organizations by creating a blueprint of their different dimensions - their linkages, imperatives, compulsions and the constraints that drive their structure and operations. In this context, the blueprint model introduced by these two types includes the areas of mission, structure, financing, recruitment, and propagation. The model shows the sequencing between the various areas of management with the options chosen by rational leadership in terms of the better fitting according to the internal and external environments and resources at their disposal. An analysis of such progression that results in the internal organization and the capabilities of the entities can then be deployed by the counterterrorism agencies to identify and home in on the specific weak points for optimal results. This Model can be further enhanced to include other areas that would help in creating blueprints for specific terrorist entities operating in any specific environment.
Keywords: terrorism; counterterrorism; jihadist; ISIS; strategy